Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae) - Ng, Heok Hee; Siebert, Darrell J. (Zootaxa, 2005)
Pseudomystus stenogrammus, a new species of bagrid catfish, is described from the Barito River drainage of southern Borneo. The new species is distinguished from all congeners by its colour pattern.